2009
DOI: 10.3102/0002831208326559
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mathematics for Understanding: An Analysis of Lessons Submitted by Teachers Seeking NBPTS Certification

Abstract: The authors present an analysis of portfolio entries submitted by candidates seeking certification by the National Board for Professional Teaching Standards in the area of Early Adolescence/Mathematics. Analyses of mathematical features revealed that the tasks used in instruction included a range of mathematics topics but were not consistently intellectually challenging. Analyses of key pedagogical features of the lesson materials showed that tasks involved hands-on activities or real-world contexts and techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 26 publications
(41 reference statements)
1
33
0
1
Order By: Relevance
“…Intrinsic motivation, openness, curiosity, and autonomy often play a role in children's creative efforts (Runco, 2006). Silver, Mesa, Morris, Star, and Benken (2009) found that experienced teachers have many aims when choosing tasks, including the aim of building students' self-confidence, which is negatively correlated with anxiety (Silver et al, 2009). …”
Section: Self-regulation and Self-efficacy -One Of The Affective Aspementioning
confidence: 99%
“…Intrinsic motivation, openness, curiosity, and autonomy often play a role in children's creative efforts (Runco, 2006). Silver, Mesa, Morris, Star, and Benken (2009) found that experienced teachers have many aims when choosing tasks, including the aim of building students' self-confidence, which is negatively correlated with anxiety (Silver et al, 2009). …”
Section: Self-regulation and Self-efficacy -One Of The Affective Aspementioning
confidence: 99%
“…As BorgfordParnell et al (2010) emphasized, design often involves working on complex and ill-structured problems that feature ambiguity, multiple solutions, and few, if any, defined rules. The importance of middle school students working on challenging and motivating learning experiences with high cognitive demand has been stressed repeatedly in the literature (e.g., Brophy et al, 2008;Lambert & Stylianou, 2013;Silver, Mesa, Morris, Star & Benken, 2009;Stoner, et al, 2013), with such experiences contributing to the development of creative, flexible, and innovative thinking skills. Students are thus better placed to deal with the complex issues that arise in their present and future lives, including those that involve mathematical and scientific situations (e.g., Borgford et al, 2010;English, Dawes, Hudson, & Byers, 2009;National Research Council, 2009a).…”
Section: Engineering Design Processes In K-12 Educationmentioning
confidence: 99%
“…Despite good intentions and well-laid conceptual foundations, many educational reform movements have failed to produce fundamental changes in the teaching practices of individual teachers (Cohen, 1990;Jacobs et al, 2006;Rousseau, 2004;Spillane, 2004;Spillane & Zeuli, 1999;Warfield, Wood, & Lehman, 2005). In the United States, for example, mathematics teaching generally looks and feels much as it has over the last 50 years; a classroom where sense-making is overshadowed by an emphasis on using standard procedures and getting the correct answers (Hiebert, 2013;Hiebert et al, 2005;Hoetker & Ahlbrand, 1969;Silver, Mesa, Morris, Star, & Benken, 2009). In Europe, despite a general increase in positive attitude towards inquiry-based practices in science and mathematics, survey data suggest that implementation of such practices varies widely by country (Engeln, Euler, & Maass, 2013).…”
Section: Introductionmentioning
confidence: 99%